Numerical investigation on crack branching during collision for rock-like material. (April 2015) - Yang, Y.F.; Li, G.; Liang, Z.Z.; Tang, C.A.
Highlights: A precrack rock specimen loaded by impact was used as the subject of study. The interaction between the impactor and the specimen was considered. Branching cracks induced by impact was analysed. The effects of heterogeneity on the crack propagation were investigated. Abstract: In this study, a rock specimen with a single notch was used as the subject of study in edge-impact experiments. Based on the principle of elastic-brittle damage evolution, crack curving and branching mechanisms of rock-like materials under dynamic shear stress were studied through the adoption of a numerical simulation method. The numerical simulation results not only reflect the experimental trends but also permit further extension and expansion from the foundation of the physical tests. The effects of different heterogeneous rock on the crack propagation were considered. The results can provide some valuable reference for studies on the dynamic failure characteristics of rock-like material.